Efektivitas Penambahan Molase dan Sari Tebu Sebagai Sumber Karbohidrat Terhadap Kelimpahan Plankton dan Performa Ikan Nila (Oreochromis nIloticus) Dalam Sistem Bioflok - Chairunisa, Triyana; Sukarti, Komsanah; Almady, Ismail Fahmy; Pagoray, Henny; Nikhlani, Andi; Fitriyana, Fitriyana (Universitas Batangahari Jambi, 2024)
The current concept of aquaculture technology development prioritizes zero waste discharge fish/shrimp production systems through an in situ biofiltration process to maintain water quality and recycle aquaculture waste into a highly nutritious supplementary feed source. This study aims to 1) Analyze the abundance, diversity, and dominance of plakton in tilapia rearing tanks of biofloc system with the addition of molasses and sugarcane juice as carbohydrate sources, 2) Analyzing the growth rate of tilapia specifications, weight growth, and length of tilapia (O.niloticus) in biofloc systems treated with the addition of molasses and sugarcane juice as a carbohydrate source. This study used the t-student test with a confidence level of 95%, with 2 treatments namely; P1 giving molasses; P2 giving sugarcane juice. The results showed that the addition of different carbohydrate sources in tilapia enlargement resulted in the highest tilapia weight growth in the P1 treatment with the addition of molasses has an average value of 32.97 g. P2 treatment with the addition of sugar cane juice has an average value of 24.55 g. In length growth has the highest average value in the P1 treatment given the addition of molasses which is 2.37 cm while for P2 with sugar cane juice treatment has a value of 2.27cm. The specific growth rate of tilapia was highest in the P2 treatment with an average value of 1.79% / day, while the P1 treatment had an average value of 1.51% / day. From the results of statistical analysis on weight growth and specific growth of tilapia significantly different but not significantly different from the growth of tilapia length. Plankton abundance in this study showed differences in each treatment, the results of observations from research for 30 days found data that the treatment of molasses has a plankton abundance value of 3780 individual plankton / l while for the treatment of sugar cane juice has a value of 2772 individual plankton / l. The conclusion of this study is the abundance of plankton in the fish tank. The conclusion of this study is that the abundance of plankton in the molasses pond treatment shows more diverse results and a higher abundance index compared to the sugar cane juice treatment, so the molasses-treated pond shows more fertile waters than the sugar cane juice treatment. Then for the growth of length and weight of tilapia given additional molasses showed better results than sugar cane juice, due to the addition of molasses can accelerate the growth of tilapia